Precipitation chemistry and wet deposition in Kruger National Park, South Africa - Mphepya, J. N.; Galy-Lacaux, C.; Lacaux, J. P.; Held, G.; Pienaar, J. J. (Springer, 2006)
The chemical composition, as well as the sources contributing to rainwater chemistry have been determined at Skukuza, in the Kruger National Park, South Africa. Major inorganic and organic ions were determined in 93 rainwater samples collected using an automated wet-only sampler from July 1999 to June 2002. The results indicate that the rain is acidic and the averaged precipitation pH was 4.72. This acidity results from a mixture of mineral acids (82%, of which 50% is H2SO4) and organic acids (18%). Most of the H2SO4 component can be attributed to the emissions of sulphur dioxide from the industrial region on the Highveld. The wet deposition of S and N is 5.9 kgS.ha(-1).yr(-1) and 2.8 kgN.ha(-1).yr(-1), respectively. The N deposition was mainly in the form of NH4+. Terrigenous, sea salt component, nitrogenous and anthropogenic pollutants have been identified as potential sources of chemical components in rainwater. The results are compared to observations from other African regions.
Keywords: precipitation chemistry; wet deposition; acid rain; semi-arid savanna; South Africa